Modelagem geométrica do conversor buck-boost não-inversor usado na interface de nanorrede CC residencial - Ribeiro, Gustavo Colpes (2021)
This dissertation presents the control system for a DC-Nanogrid based on the DCBus Signalling technique. Converter principle of operation is described and its control loops are designed. Modulation geometric approach is used in order to simplify the mathematical modelling and its inner current loop. In order to maximize the power extracted from the photovoltaic arrangement, a maximum power point tracking algorithm is implemented in a indirect way, regulating the input DC-bus voltage. NIBB converter operates in closed loop, using a faster inner inductor current, using the voltage across the inductor as control variable as well as two outer voltage slower loops, so it would be possible to regulate both input and output voltages (V1 and V2). Both simulation and experimental results corroborate the theoretical analysis about the efficiency improving on the BBNI converter as it can be modulated by modifying a auxiliar voltage, adding a degree of freedom in the PWM modulation.